Facile syntheses of conjugated polymers for photothermal tumour therapy - Peiyao Chen (Nature Portfolio, 2019)
Conjugated polymers are of interest for photothermal applications; however, synthesis of these polymers can be complex. Here, the authors report on a facile synthesis method that uses a modified CBT-Cys click reaction to make conjugated polymers and test these polymers for photothermal therapy applications.